Analysis of needs for the development of BIPA teaching materials: Listening skills - Merlin Yupitasari; Diah Latifah; Halimah Halimah (Inovasi Kurikulum, 2024)
The development of Indonesian language teaching materials requires the application of technology to make it easier for students to receive lessons. This research analyzes the need to develop teaching materials for Indonesian listening skills for foreign speakers (BIPA). The research method used is quantitative with a descriptive approach. Data was collected by filling out questionnaires by 10 BIPA teachers from various institutions and observing relevant teaching manuals. The analysis results show that most respondents have taught BIPA for over five years and use audio and video media in listening learning. They stated that they needed interactive listening media and used materials from the institutions where they taught more often, even though they found several areas for improvement in the quality and suitability of the materials. Most respondents also expressed their readiness to be contacted further regarding this research. Data analysis also revealed respondents' preferences for using digital based media to learn to listen to BIPA, with most respondents using platforms such as YouTube and Zoom Meet. These findings provide in-depth insight into teachers' preferences and needs in developing BIPA listening teaching materials and the importance of adapting learning materials to students' needs.   Abstrak Pengembangan bahan ajar Bahasa Indonesia perlu mengaplikasikan perkembangan teknologi supaya memudahkan pemelajar menerima pelajaran. Penelitian ini bertujuan untuk menganalisis kebutuhan pengembangan bahan ajar keterampilan menyimak Bahasa Indonesia bagi Penutur Asing (BIPA). Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan deskriptif. Data dikumpulkan melalui pengisian kuesioner oleh 10 guru BIPA dari berbagai institusi dan observasi terhadap buku pedoman pengajaran yang relevan. Hasil analisis menunjukkan bahwa mayoritas responden telah mengajar BIPA selama lebih dari 5 tahun dan menggunakan baik media audio maupun video dalam pembelajaran menyimak. Mereka mengatakan membutuhkan media menyimak interaktif dan lebih sering menggunakan materi dari instansi tempat mereka mengajar, meskipun menemukan beberapa kekurangan dalam kualitas dan kesesuaian materi. Sebagian besar responden juga menyatakan kesiapannya untuk dihubungi lebih lanjut terkait penelitian ini. Analisis data juga mengungkapkan preferensi responden terhadap penggunaan media berbasis digital dalam pembelajaran menyimak BIPA, dengan mayoritas responden menggunakan platform seperti YouTube dan Zoom Meet. Temuan ini memberikan wawasan mendalam tentang preferensi dan kebutuhan pengajar dalam pengembangan bahan ajar menyimak BIPA, serta pentingnya penyesuaian materi pembelajaran dengan kebutuhan pemelajar. Kata Kunci: BIPA; menyimak; pengembangan bahan ajar